BOOK REVIEW: CANDY FLOSS COLLECTION (3 NOVELS) BY PATRICIA LEAVY IS A TRIUMPHANT WORK OF ART - Anyiwo, U. Melissa (Art/Research International)

(untitled) (University of Alberta, 2021)
Leading methodologist and arts-based researcher, Patricia Leavy, pioneered the method of social fiction, fiction-based research, or fiction as a research practice. Her latest release, Candy Floss Collection, is a set of three previously published novels, which together form installation art. This definitive and beautifully rendered work is important for several reasons. First, it demonstrates the power of fiction as a research method. Second, it is a beautiful piece of art. Third, it centres on powerful content, telling important and often invisible stories about women’s lives, aspirations, relationships, and daily struggles. Finally, this collection is a well-crafted piece of public scholarship that is imminently accessible to audiences inside and outside of academia. Overall, Candy Floss Collection is a triumphant piece of art, an exemplar of fiction as research, a highly accessible piece of public scholarship, and an engaging read. This is a significant and even game-changing work and ought to be recognized as such.